1997
DOI: 10.1523/jneurosci.17-15-05858.1997
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Ultrastructural Analysis of Hippocampal Excitatory Synapses

Abstract: From three-dimensional reconstructions of CA1 excitatory synapses in the rodent hippocampus and in culture, we have estimated statistical distributions of active zone and postsynaptic density (PSD) sizes (average area ϳ0.04 m 2 ), the number of active zones per bouton (usually one), the number of docked vesicles per active zone (ϳ10), and the total number of vesicles per bouton (ϳ200), and we have determined relationships between these quantities, all of which vary from synapse to synapse but are highly correl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

112
770
7
2

Year Published

1999
1999
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 885 publications
(891 citation statements)
references
References 47 publications
112
770
7
2
Order By: Relevance
“…It has been shown that most hippocampal glutamatergic axon terminals have only one synaptic specialization and that a single specialization contains a large number of docked vesicles (Sorra and Harris, 1993;Schikorski and Stevens, 1997). Indeed, we also found only one presynaptic specialization at each axon terminal and a large number of small synaptic vesicles attached to the presynaptic specialization at identified synaptic contacts.…”
Section: Discussionsupporting
confidence: 63%
“…It has been shown that most hippocampal glutamatergic axon terminals have only one synaptic specialization and that a single specialization contains a large number of docked vesicles (Sorra and Harris, 1993;Schikorski and Stevens, 1997). Indeed, we also found only one presynaptic specialization at each axon terminal and a large number of small synaptic vesicles attached to the presynaptic specialization at identified synaptic contacts.…”
Section: Discussionsupporting
confidence: 63%
“…At hippocampal synapses, D = 0.0042 µm 2 /s (Shtrahman et al, 2005) and  = 38 nm (Harris and Sultan, 1995). Vesicle density averages 1,800-3,100 v/µm 3 (Harris and Stevens, 1989;Schikorski and Stevens, 1997), but only 15% are mobile (Shtrahman et al, 2005), yielding an effective range for  of 270-465 v/µm 3 . From these values, the formula predicts a maximum kinetics of vesicle resupply from the cytoplasm of  = 13-23 s. For comparison, replenishment at hippocampal synapses involves a fast process with  7 s and a slower process with  1 min; the slower process is thought to reflect the kinetics of resupply to the readily releasable pool (Stevens and Wesseling, 1998;Wesseling and Lo, 2002;Garcia-Perez and Wesseling, 2008).…”
Section: Comparisons With Other Synapsesmentioning
confidence: 99%
“…We performed two measures of the length of the axon-spine interfaces. The first one was limited to the active zone (AZ), composed of the synaptic cleft bordered by vesicles on the presynaptic axonal bouton and corresponding to the postsynaptic density (PSD) on the dendritic spine (Schikorski and Stevens, 1997). The second measure, including the active zone, was extended to the nonsynaptic interface, characterized by the thin extracellular space bordered by spine and bouton membranes without specialization.…”
Section: Electron Microscopymentioning
confidence: 99%